Advances in Autophagy–Lysosomal Pathway and Neurodegeneration via Brain–Gut Axis - Ping Yao; Hailong Han (Biomedicines, 2025)
Background/Objectives: The autophagy–lysosomal pathway (ALP) is crucial for neuronal health by clearing misfolded proteins and damaged organelles. While much research has focused on ALP dysfunction in the central nervous system, new evidence shows its importance in the gut, where it affects neurodegeneration via the gut–brain axis. Past reviews have mainly studied the ALP’s direct neuroprotective effects or the gut microbiota’s role in neurodegeneration separately. However, the two-way relationship between the ALP and the gut microbiota in neurodegenerative diseases is not well understood. We combine the latest findings on the ALP’s role in gut health, microbial imbalance, and neuroinflammation, providing a comprehensive view of their combined effects in Alzheimer’s, Parkinson’s, and Huntington’s diseases. Methods: This narrative review synthesizes evidence from preclinical, clinical, and translational studies (2014–2025) to explore the interplay between the autophagy–lysosomal pathway (ALP) and the gut–brain axis in neurodegeneration. The literature was identified via PubMed and Web of Science using search terms including autophagy, lysosome, gut microbiota, neurodegeneration, and gut–brain axis, with additional manual screening of reference lists. The inclusion criteria prioritized studies elucidating molecular mechanisms (e.g., ALP–microbiota crosstalk), while excluding case reports or non-peer-reviewed sources. Results: The gut–brain axis facilitates bidirectional communication between the gut and the brain through neural, immune, and metabolic pathways. Autophagy dysfunction may disrupt intestinal homeostasis, promote gut microbiota dysbiosis, and trigger chronic neuroinflammation, ultimately accelerating neurodegeneration. Notably, strategies targeting the gut microbiota and restoring intestinal barrier function via the ALP have demonstrated promising potential in delaying the progression of neurodegenerative diseases. Conclusions: This review establishes the ALP as a dynamic regulator of gut–brain communication, highlighting microbiota-targeted therapies as promising strategies for neurodegeneration.